Characterizing microbial diversity and metabolic pathways in yak milk and fermented yak milk based on metagenomics: A study from Ganzi Tibetan autonomous prefecture - Jie Zhang; Yangbo Jiao; Kaiyang Liu; Wenyou Situ; Bilige Menghe; Yongfu Chen; Musu Zha (Food Chemistry: X)
Kangding and Litang are the capital and pivotal county respectively within Ganzi. The region's distinctive geographical and climatic environment has endowed yak milk (YM) and its products with unique microbial resources, which play a crucial role in product quality and flavor. Therefore, it is important to understand their microbiota. We analyzed microbiota and metabolic pathways in YM. Results revealed 207 species, with Pseudomonas unclassified, Acinetobacter johnsonii dominant in YM, and Lactobacillus delbrueckii, Streptococcus thermophilus in fermented yak milk (FYM). YM exhibited lower microbial and bacteriophage diversity. Bacteriophage diversity was primarily targeting harmful microbes. Yak and camel milk showed similarities, while koumiss and fermented camel milk shared dominant bacteria. Metabolic pathways in YM were enriched with carbohydrates, amino acids, fats, and purine metabolism. In conclusion, this study provides information on the microbial resources and related metabolic pathways in yak milk and naturally fermented yak milk in the Ganzi region of China.